The Structure of Conscious Experience - Beach, Lee Roy (Cambridge Scholars Publisher, 2019)
There must exist a point at which the molecular and electro-chemical processes that comprise brain function are transformed into rich, orderly conscious experience which seamlessly blends the present moment, what led up to it, and what will follow it. This is the stuff of our everyday lives, and it raises questions about its organization and how that organization facilitates engagement with the world at large. In short, what is the structure of conscious experience and what is gained by it being structured that way?This book argues that the structure is what is familiarly known as narrative fo.